Mycotypha indica P.M. Kirk & Benny, in turkey dung, a new record for Venezuela - Delgado ívila, Adolfredo E; Urdaneta García, Lilia M; Piñeiro Chávez, Albino J (Multiciencias, 1970)
On the basis of a study of coprophilous fungi from Zulia state,Venezuela, a Mycotyphaceae(Mucorales) Zygomycota with umbranched sporophores at first, often secondarily branched; more or less erect, up to 3-4mmhigh, 6-8 Î¼m diam; hyaline at first, becoming pale blush gray, non-septate distally below the fertile vesicle. It is variable in length, ovoid to long-cylindrical minutely roughened; without sporangiola, rounded at apex, sporangiola dimorphic and borne in the outer row, are obvoid sporangiospores of similar size and shape to the sporangiola. Substrate hyphae branched, no septate at first, becoming irregularly septate, giving rise to hyaline, globose, yeast-like budding cells, occasional cell segments forming chlamydospores. Zygospores abundant, formed on aerial hyphae near surface of substrate; globose to subglobose, suspensors opposed, anisogamus, smooth, hyaline to pale gray. Homothallic. Colonias on Meye medium of 4-6 cm diam, in 10-12 days at 22-24°C; turf dense, more or less zonate, mouse gray color. The species was identified as Mycotypha indica, in turkey dung, which represents a new record from Venezuela.